2013
DOI: 10.1016/j.ympev.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogeny of the avian family Alaudidae (larks) reveals complex morphological evolution, non-monophyletic genera and hidden species diversity

Abstract: The Alaudidae (larks) is a large family of songbirds in the superfamily Sylvioidea. Larks are cosmopolitan, although species-level diversity is by far largest in Africa, followed by Eurasia, whereas Australasia and the New World have only one species each. The present study is the first comprehensive phylogeny of the Alaudidae. It includes 83.5% of all species and representatives from all recognised genera, and was based on two mitochondrial and three nuclear loci (in total 6.4 kbp, although not all loci were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 62 publications
(87 reference statements)
2
65
0
1
Order By: Relevance
“…Recent studies have revealed considerable hidden diversity in some taxa, such as Mirafra assamica, which was proposed to be split into four species based mainly on vocal, behavioral and morphological data (Alström, 1998; corroborated by molecular study by Alström et al, 2013); the Calendulauda (previously Certhilauda) albescens complex, which was suggested to consist of three instead of two species based on mitochondrial, morphological and vocal data (Ryan et al, 1998); the Certhilauda curvirostris complex, which was recommended to be treated as five instead of one species based on mitochondrial and morphological evidence (Ryan and Bloomer, 1999); and Galerida cristata, which was shown to consist of two partly sympatric and largely reproductively isolated species in Morocco, G. cristata sensu stricto and G. macrorhyncha (Guillaumet et al, 2005(Guillaumet et al, , 2006(Guillaumet et al, , 2008. In an analysis of mitochondrial data, Alström et al (2013) found several unexpectedly deep divergences between taxa presently treated as conspecific (e.g. within Ammomanes cinctura, Ammomanes deserti, Calandrella brachydactyla, Eremophila alpestris), but also some shallow splits between currently recognized species (e.g.…”
Section: Alaudidaementioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have revealed considerable hidden diversity in some taxa, such as Mirafra assamica, which was proposed to be split into four species based mainly on vocal, behavioral and morphological data (Alström, 1998; corroborated by molecular study by Alström et al, 2013); the Calendulauda (previously Certhilauda) albescens complex, which was suggested to consist of three instead of two species based on mitochondrial, morphological and vocal data (Ryan et al, 1998); the Certhilauda curvirostris complex, which was recommended to be treated as five instead of one species based on mitochondrial and morphological evidence (Ryan and Bloomer, 1999); and Galerida cristata, which was shown to consist of two partly sympatric and largely reproductively isolated species in Morocco, G. cristata sensu stricto and G. macrorhyncha (Guillaumet et al, 2005(Guillaumet et al, , 2006(Guillaumet et al, , 2008. In an analysis of mitochondrial data, Alström et al (2013) found several unexpectedly deep divergences between taxa presently treated as conspecific (e.g. within Ammomanes cinctura, Ammomanes deserti, Calandrella brachydactyla, Eremophila alpestris), but also some shallow splits between currently recognized species (e.g.…”
Section: Alaudidaementioning
confidence: 99%
“…However, a phylogeny including 81 of the 97 species and representatives of all 21 recognized genera, based on two mitochondrial and three nuclear loci has just appeared (Alström et al, 2013). The latter has revealed many unpredicted relationships, including some non-monophyletic genera (Calandrella, Mirafra, Melanocorypha, Spizocorys), and proposed a revised generic classification.…”
Section: Alaudidaementioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial genomes have become the most widely used molecular markers among a broad array of molecular evolutionary and phylogenetic studies (Rong et al 2016). Several molecular phylogeny of the Alaudidae has been published, based on mitochondrial and nuclear sequences from mostly larks species (Tieleman et al 2003;Alstr€ om et al 2013). However, only one complete mitochondrial genome, Eurasian Skylark Alauda arvensis (under accession no.JQ322641, Qian et al 2013), is available in GenBank.…”
Section: Mitogenome Announcementmentioning
confidence: 99%